THE INFLUENCE OF FITRAT AND JADIDISM ON LITERARY STUDIES - Ziyodullaev Shamsiddin Yusuf ugli (Bright Mind Publishing, 2025)
The topic of "The Influence of Fitrat and Jadidism on Literary Studies" addresses an important issue regarding the role, impact, and new methodologies introduced by the Fitrat and Jadidism movements in literary scholarship. Emerging at the turn of the 19th and 20th centuries, these movements played a crucial role in advancing literary, social, and political innovations in Uzbek literature. They significantly influenced the development of the Uzbek language, culture, and literary styles. Jadidism, in particular, introduced new literary forms and implemented scientific-pedagogical approaches in translation and original literary production. This study focuses especially on Fitrat’s innovative ideas in literary studies, the influence of Jadidism, and their social and spiritual impact on Uzbek literature.
Keywords: Jadidism, literary studies, innovation, social influence, culture, Uzbek literature, translation, literary style, modernization, 19th century, 20th century.